Perceptions on the role of the Sixth Form Tutor: Sixth Form Students and Tutors Own Voices - Henderson, Sonia (2017)
Many studies have highlighted the beneficial role a tutor can have for secondary students; from providers of emotional care, to supporters of learning and overall progress monitors. The tutor appears to occupy a special position within secondary schools however, there have been very few attempts to examine the role of a tutor within a Sixth Form context. The aim of this study was to give a voice to Sixth Form students and tutors in relation to their perceptions of the role a tutor has during the demanding last two years of formal education. Semi structured, one-on-one interviews were conducted with 10 Sixth Form tutors and 4 focus group interviews took place with a total of 44 Sixth Form students. The data was thematically analysed and six common themes were identified, which provided a deep insight into the participants’ perceptions of the role of the Sixth Form tutor. The findings of this study provide some support for previous literature, as it concludes that tutors can be beneficial aspect of pastoral care but perhaps not to the same extent as in secondary school and their success appears to greatly depend on the quality of the relationship between the tutor and tutee.